The effect of combined sport massage and proprioceptive neuromuscular facilitation on reducing muscle spasm pain in martial arts athletes - Rifky Hidayatullah; Baiq Satrianingsih; Lalu Suprawesta (Sriwijaya Journal of Sport, 2026)
Research Problems: Muscle spasm pain is a musculoskeletal disorder frequently experienced by martial arts athletes due to repetitive high-intensity physical activity. This condition may reduce performance in training and competition because it causes pain, muscle stiffness, and limited mobility. Sport Massage and proprioceptive neuromuscular facilitation (PNF) are non-pharmacological recovery methods used to promote muscle relaxation and improve neuromuscular function. Research Objectives:  This study aimed to determine the differences in the effectiveness of Sport Massage, PNF, and their combination in reducing muscle spasm pain among martial arts athletes. Methods: This study employed a quasi-experimental, three-group pretest-posttest design. The sample consisted of 24 martial arts athletes selected through purposive sampling and divided into three groups: Sport Massage, PNF, and combination groups. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after treatment. Data were analyzed using paired t-test and one-way ANOVA. Results: The results showed that all groups experienced a reduction in muscle spasm pain after treatment at a significance level of 0.05. Conclusion: The One-Way ANOVA test indicated a significant difference among groups with a significance value of 0.004. The combination group showed a greater reduction in muscle spasm pain compared with the sport massage and PNF groups. Therefore, the combination of Sport Massage and PNF can be used as an alternative recovery intervention to reduce muscle spasm pain and support the recovery process of martial arts athletes.